Model species in evo‐devo: a philosophical perspective. Issue 1 (6th January 2014) - Bolker, Jessica A.
SUMMARY A model is a representation of or an analogy for something else; in a biological context, the term often refers to organisms or species that serve as a widely used platform for experimental research. In developmental biology, an extraordinarily detailed understanding of fundamental genes and mechanisms has been built around a few core models including Drosophila, mouse, Caenorhabditis elegans, Arabidopsis, and zebrafish. The use of model species entails a series of epistemological issues and commitments regarding similarity, generalization, and the balance between representation and accessibility. In addition, the power of a given model is highly context‐dependent, and the core models of developmental biology may not suffice for evo‐devo questions. An epistemological perspective can clarify the complementary roles of standard and emerging models in evo‐devo, as well as inform decisions about when new models are needed, and criteria for choosing them.